Towards integrated assessment and advice in small-scale fisheries : principles and processes - Garcia, Serge; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2008)
The document presents the principles and processes for integrated assessment and advice in small-scale fisheries. The first chapter discusses failures of conventional assessment and management approaches. Chapter 2 presents the conceptual origins and principles of integrated assessment of small-scale fisheries. The framework is then introduced and places the assessment within the broader planning and management cycle. The final chapter discusses the implementation of the IAA framework.--Publisher's description
Keywords: Small-scale fisheries